MY CART (5)

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price:

There are no items in this cart.
Continue Shopping
                   

plz solve -


Lt(x->0) (log(cos x)/(sinx)^2)


thanx in advance..

3 years ago

Share

Answers : (2)

                                        

Lt x->0 log(cos x)/ (sinx)2


Lt x->0 log [1 + (cosx - 1)]/(sinx)2                                         {Add and subtract 1}


Lt x->0 log [1 + (cosx - 1)](cosx - 1)/ (cosx - 1) (sin x)2          {Multiply divide by (cosx - 1)}


Lt x->0 {log [1 + (cosx - 1)]/ (cos x - 1)}  {(cosx - 1) / (sinx)2}


Lt x->0 {(log [1 + m])/ (m)} { - (1 - cosx)/ ??(sinx)2}


 Here m->0 as cosx - 1 ->0 when x-> o So, Standard limit Lt x->0  log[ 1 + x]/ x = 1


Lt x->0 {1} {- (1 - cosx)(x2) / (x2) (sinx)2                                            {Multiply divide by (sinx)2}


Lt x->0 - {(1- cosx) / (x2)} { (x2) / (sinx)2}


Using Standard limit Lt x->0 (1-cosx) / (x2) = 1/2 and Lt x->0  (x/ sinx)= 1, we get,


Lt x->0 - {1/2} { (1)2 }


Lt x->0 -1/2


= -1/2

3 years ago
                                        

Anmol , Ur answer is indeed right . but I want to do it by a simple method called L Hopitals rule.


Any problem yielding 0/0 by direct substition can be solved by the approach.


This method coveys tht any  limit yielding 0/0


lim f(x)/g(x) = {d f(x) /dx } / {d g(x) /dx }


Here in the question by direct substitution we get 0/0 So apply L Hopitals rule


Lt (x->0) log(cos(x))/(sinx)2 = Lt(x->0)d/dx {log(cos(x))} / d/dx {sin2x} = -1/2 cos2(x)  = -1/2 (By direct Substitution)

3 years ago

Post Your Answer

More Questions On Algebra

Ask Experts

Have any Question? Ask Experts

Post Question

 
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!!
Click Here for details
x 1/2 +y=11,x+y 1/2=7
 
 
Hello student, Please find the answer to your question below From(1): x^(1/2) = 7 - y , Letx (1/2) +y=11...........(1) x+y (1/2) =7..........(2) Squaring both sides: x = (7-y)^2 = y^2 - 14y...
  img
SHAIK AASIF AHAMED 7 months ago
prove that n 3 + 3n 2 + 5n + 3 is divisible by 3 for any natural number n
 
 
Hello Student, n^3 + 3n^2 + 5n + 3 =n^3 + 3n^2 + 2n+3n + 3 =n(n^2 + 3n + 2)+3n + 3 =n(n+1)(n+2)+3n+3 Prooved Thanks & Regards Arun Kumar Btech, IIT Delhi Askiitians Faculty
  img
Arun Kumar 9 months ago
 
By Fermat’s theorem, n 3 -n is divisible by 3. Hence n 3 +3n 2 +5n+3 = (n 3 -n)+(3n 2 +6n+3) = 3m+3(n+1) 2 for some integer m making the expression obviously a multiple of 3.
 
mycroft holmes 9 months ago
question is in image
 
 
Using logarithm property the given equation can be written as: Also using the domain of log x which is define only when x > 0 , we get from three log functions that x > -2 , x <4...
  img
Satyajit Samal 7 months ago
x=a cos( theta) + b sin(theta) y=a sin(theta) – b cos( theta) prove that y*y2-x*y1+y=0
 
 
Ans: Hello Student, Please find answer to your question below Differentiate Differentiate
  img
Jitender Singh 8 months ago
Find an equation of the angle bisector of the obtuse angles formed by the lines 2x+6y= 9 and x-3y= -2. sketch the given lines and angle bisector.
 
 
Find the angle between the 2 lines and the point of intersection. Use this angle to find the slope of the angle bisector by adding/subtracting the angle from the slopes of the 2 lines. You...
  img
Ravi 5 months ago
( * ) If A,B,C are acture angles such that sin (B+C-A) = cos(C+A-B) = tan(A+B-C) = 1 then (A,B,C)=
 
 
Hello student, Please find the answer to your question below sin (B+C-A) =1 => B+C-A = 90 ….….(1) cos(C+A-B) = 1 => C+A-B= 0….…..(2) tan(A+B-C) = 1 =>...
  img
Nishant Vora 7 months ago
View all Questions »